Experimental study on the mechanical properties, acoustic emission characteristics, and permeability evolution of sandstone under triaxial hydromechanical coupling. Issue 12 (23rd August 2022) - Wang, Guozhu; Song, Lei; Wang, Qirui; Tian, Zhuangcai; Fan, Junqi; Wang, Yu; Ren, Jianwei; Yang, Weihao; Li, Haipeng; Zhang, Mingwei; Shen, Honglei
Abstract: In situ stress and groundwater have important effects on the deformation and stability of deep underground rock masses. Therefore, it is extremely important to study the mechanical properties and permeability evolutionary processes of rocks under hydromechanical (HM) coupling. The purpose of this study was to investigate the mechanical properties and permeability evolution of sandstone using triaxial compression tests under different confining and seepage pressures. The test results show that the confining pressure can increase the strength of sandstone, whereas the seepage pressure has the opposite effect. The initial and maximum permeabilities were positively correlated with seepage pressure and negatively correlated with confining pressure. The confining and seepage pressures had little effect on the change in initial permeability. As a common parameter of acoustic emission (AE), cumulative AE counts can intuitively reflect the permeability evolutionary process in the sandstone failure process. A permeability evolutionary early warning model for the sandstone failure process under HM coupling is proposed. The results are helpful for understanding the influence of in situ stress and seepage pressure on deep sandstone and the permeability evolutionary mechanism, and they can be used to provide early warning of water inrush disasters in deep underground structures. Abstract : The purpose of this study is to study the mechanical properties and permeability evolution of sandstone by triaxial compression tests under different confining and seepage pressures. In addition, a permeability evolutionary early warning model for the sandstone failure process under hydromechanical coupling is proposed. The results are helpful for understanding the influence of in‐situ stress and seepage pressure on deep sandstone and the permeability evolutionary mechanism, and can be applied to the early warning of water inrush disasters in deep underground structures